2022
DOI: 10.1126/sciadv.abn2082
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial versus pronephron fate decision is modulated by the transcription factors Cloche/Npas4l, Tal1, and Lmo2

Abstract: Endothelial specification is a key event during embryogenesis; however, when, and how, endothelial cells separate from other lineages is poorly understood. In zebrafish, Npas4l is indispensable for endothelial specification by inducing the expression of the transcription factor genes etsrp , tal1 , and lmo2 . We generated a knock-in reporter in zebrafish npas4l to visualize endothelial progenitors and their derivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 86 publications
2
15
0
Order By: Relevance
“…In npas4l mutants, we observed expanded glomerular precursors and pronephron tubules (Fig. 4C), similar to defects seen in hand2 mutants (Perens et al, 2016) and consistent with previously characterized npas4l mutant pronephron phenotypes (Majumdar & Drummond, 1999; Mattonet et al, 2022). Remarkably, in npas4l ; osr1 double mutants, glomerular precursors and pronephron tubules appeared most similar to wild-type embryos (Fig.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…In npas4l mutants, we observed expanded glomerular precursors and pronephron tubules (Fig. 4C), similar to defects seen in hand2 mutants (Perens et al, 2016) and consistent with previously characterized npas4l mutant pronephron phenotypes (Majumdar & Drummond, 1999; Mattonet et al, 2022). Remarkably, in npas4l ; osr1 double mutants, glomerular precursors and pronephron tubules appeared most similar to wild-type embryos (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Last, hand2 and osr1 expression mark the lateral territory. Some progenitors within this lateral territory continue to express hand2 and migrate medially (Yin et al, 2010), giving rise to derivatives that include the mesothelium (Prummel et al, 2022). Notably, hand2 is an essential and potent inhibitor of IM fate within this territory; we have only observed ectopic Pax2a expression in this territory in hand2 mutants, but not in npas4l loss-of-function or osr1 overexpression scenarios.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…We asked whether the expression of npas4l , arnt1 and arnt2 was the same in the anterior LPM (ALPM) and posterior LPM (PLPM). npas4l and its associated downstream targets exhibit more expression in the PLPM compared to the ALPM in embryos throughout segmentation (Liao et al, 1997; Liao et al, 2000; Marass et al, 2019; Mattonet et al, 2022; Qian et al, 2005; Stainier et al, 1995). At 4- 6 somite stage embryos, we found that expression of npas4l and arnt2 was greater in the PLPM than in the ALPM, but the expression of arnt1 was similar in both regions ( Figure S3C, S3E, npas4l Welsh’s t- test, p<0.0001; arnt2 Welsh’s t-test, p<0.005 ).…”
Section: Resultsmentioning
confidence: 99%